Rapporter - Ringsager, Kristine; Bjørnseth Kristensen, Thomas; Wessel, Jan Andreas; Lønstrup, Ansa; Kaargaard Nielsen, Steen; Lundberg, Mattias; Ørbæk Jensen, Anne (Danish Yearbook of Musicology, 2011)
Research Projects Rap, Rights and Respect! A musical anthropology of hip hop, rap music, violence and freedom of expression (Kristine Ringsager) Silence/Noise of the Work – Dissonant passages in 20th-century arts and aesthetics (Thomas Bjørnsten Kristensen) The Historiography of Musical Listening (Jan Andreas Wessel) Audiovisual Culture and the Good Sound (Ansa Lønstrup) Conferences SoundActs, Aarhus University, September 2010 (Steen Kaargaard Nielsen) International Marcus Meibom Symposium, Stockholm, January 2010 (Mattias Lundberg) Danish Musicological Society, 2010 (Anne Ørbæk Jensen)